Arthroscopic-Assisted vs. Fluoroscopic-Only ORIF of Distal Radius Fractures: Clinical and Economic Perspectives - Wolfram Demmer; Antonina Jakob; Fabian Gilbert; Benedikt Fuchs; Sinan Mert; Nikolaus Wachtel; Riccardo Giunta; Verena Alt (Medicina)
Background and Objectives: Distal radius fractures (DRFs) are among the most common fractures globally, with a lifetime incidence of around 9%. They typically present in two age peaks: high-impact trauma in patients under 40 and low-energy trauma in those over 40. Intra-articular DRFs are classified according to the Arbeitsgemeinschaft für Osteosynthesefragen (AO) classification, influencing the treatment approach. Surgical management, particularly open reduction and internal fixation (ORIF) using volar plate osteosynthesis, is considered the gold standard. This study aims to compare the treatment costs of fluoroscopy-assisted ORIF and arthroscopy-assisted ORIF for intra-articular DRF. The analysis includes surgical procedure costs, material expenses, and operating time to evaluate the cost-effectiveness of both methods, considering reimbursement within the German healthcare system. Materials and Methods: A retrospective, monocentric study was conducted at Ludwig-Maximilians-University (LMU) Hospital, a supraregional hand trauma center in southern Germany. Patients with DRFs requiring ORIF were treated either with fluoroscopy or arthroscopic assistance. Group 1 included patients treated by the Department of Hand Surgery (Plastic Surgery), subdivided into Group 1a (arthroscopy-assisted) and Group 1b (fluoroscopy-only). Group 2 comprised patients treated by Orthopaedics and Trauma Surgery (fluoroscopy-only). Costs associated with surgical procedures, including materials, operating time, and postoperative care, were analyzed. Results: A total of 43 DRFs were treated. Group 1 consisted of 17 cases, with an average age of 49.6 years (SD = 19.4) and a 64% majority of female patients. Of these, 10 cases were treated with arthroscopy-assisted ORIF (Group 1a) and 7 with fluoroscopy-only ORIF (Group 1b). In Group 1a, the average age was 53.9 years (SD = 16.3) with 60% female and 40% male patients, while in Group 1b, the average age was 43.6 years (SD = 23.1) with 71.4% female patients. Group 2 included 25 cases, with an average age of 54.2 years (SD = 21.0) and a distribution of 64% female and 36% male patients. There was no significant difference in age and gender distribution within the groups and subgroups (p > 0.05). The mean procedure time was longer for arthroscopically assisted ORIF (111.5 min) compared to fluoroscopy-only ORIF (80.1 min), and even longer compared to Group 2 (65.0 min). Material costs were slightly higher in Group 1. Total costs for Group 1 averaged EUR 4906.58, with subgroup costs of EUR 5448.24 for arthroscopy-assisted and EUR 4132.80 for fluoroscopy-only. In comparison, Group 2 costs averaged EUR 3344.08. Conclusions: Intra-articular DRFs with severely displaced fragments or concomitant injuries benefit from arthroscopically assisted fracture treatment. While material costs do not significantly differ between arthroscopically assisted and fluoroscopy-only treatments, the significantly longer procedure time for arthroscopy-assisted ORIF results in the largest cost component. Despite this, reimbursement through the DRG system remains fixed and does not account for the increased operative duration or complexity of arthroscopic procedures. Our findings demonstrate that DRF treatment, regardless of the method used, is either not or only marginally cost-covering under the current German reimbursement structure. In the context of the ongoing shift towards outpatient hand surgery, including the management of DRF, adequate reimbursement rates are necessary to ensure the economic viability of DRF management, particularly for complex intra-articular fractures requiring arthroscopic assistance.